Wintering : The Power Of Rest And Retreat In Difficult Times - May, Katherine (New York : Riverhead Books, 2020)
"An intimate, revelatory book exploring the ways we can care for and repair ourselves when life knocks us down. Sometimes you slip through the cracks: unforeseen circumstances like an abrupt illness, the death of a loved one, a break up, or a job loss can derail a life. These periods of dislocation can be lonely and unexpected. For May, her husband fell ill, her son stopped attending school, and her own medical issues led her to leave a demanding job. Wintering explores how she not only endured this painful time, but embraced the singular opportunities it offered. A moving personal narrative shot through with lessons from literature, mythology, and the natural world, May's story offers instruction on the transformative power of rest and retreat. Illumination emerges from many sources: solstice celebrations and dormice hibernation, C.S. Lewis and Sylvia Plath, swimming in icy waters and sailing Arctic seas. Ultimately Wintering invites us to change how we relate to our own fallow times. May models an active acceptance of sadness and finds nourishment in deep retreat, joy in the hushed beauty of winter, and encouragement in understanding life as cyclical, not linear. A secular mystic, May forms a guiding philosophy for transforming the hardships that arise before the ushering in of a new season"--.
Keywords: Rest; Self-acceptance.; Nature, Healing power of